(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
Between the second and first centuries BCE, literacy experienced unprecedented growth in Hispania Citerior. The development of literacy intensified among those populations which already enjoyed a fledgling written culture and expanded into others which had been illiterate until that point. Simultaneously, the uses of writing diversified, including both the private and public spheres. This “revolution” particularly affected local languages; however, it cannot be understood without the decisive influence of Latin written culture and the political, economic, and social changes that spread throughout the province as a consequence of Roman domination.